Berlin Philharmonic concert program, 1938/1939 - Berlin Philharmoniker:::Creator::::::::::::; Oboussier, Robert, 1900-1957:::Contributor:::::::::::: (Maximilian Maetze; Germany; Berlin, 2020)
Programs for a concert by the Berlin Philharmonic conducted by Wilhelm Fürtwangler at the Festsaal der Liederhalle, Stuttgart, on May 2, 1939. The program included the Eroica Symphony.